PENYU DALAM KARYA SENI GRAFIS - Debi Jumara Putra; Irwan Irwan (Universitas Negeri Padang, 2021)
Sea turtles are turtle are found in all oceans in the world. The sea turtle is one of the ancient animals that still alive until now. The sea turtle in this work aims to visualize the form of expression or picture of the sea turtle habitats are damaged by development and plastic trash. through the technique of linoleum cut in the process of work to be one of the options the manufacture of graphic arts. After various observations as well as the work of a long created 10 works of art that can be displayed, namely : 1) Eksploitasi, 2) Terumbu sampah, 3) Terbang, 4) Kecemasan, 5) Rantai Makanan, 6) Terkurung, 7) Menetas, 8) Pencemaran, 9) Langka, 10) Ego This results in works of art Sea turtle that be a picture of the sea turtle habitat that is damaged, in addition to it's graphic works is expected to be a driving source for the creators of the otherKeywords: Sea Turtle, Linoleum cut.